2019
DOI: 10.1039/c9ra00783k
|View full text |Cite
|
Sign up to set email alerts
|

Determination and distribution of pesticides and antibiotics in agricultural soils from northern China

Abstract: Different types of soil samples from a typical farmland in northern China were collected and evaluated for the presence of the pesticides and antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Therefore, it is often detected in soil, water and other environmental samples, with concentrations ranging from μg/ml to mg/ml, it has a great health risk for people who are exposed to pesticide residues through foods 5,30 . For example, Pan et al analyzed farmland soil samples from northern China and found that the residue of DFC in the environmental samples exceeded that of 0.1 mg/kg 31 . According to the literature, the half‐life of DFC is less than 30 days and varies with different environmental conditions 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is often detected in soil, water and other environmental samples, with concentrations ranging from μg/ml to mg/ml, it has a great health risk for people who are exposed to pesticide residues through foods 5,30 . For example, Pan et al analyzed farmland soil samples from northern China and found that the residue of DFC in the environmental samples exceeded that of 0.1 mg/kg 31 . According to the literature, the half‐life of DFC is less than 30 days and varies with different environmental conditions 32,33 …”
Section: Discussionmentioning
confidence: 99%
“…The extensive use of organic compounds in the agricultural sector has led to major environmental concerns. Due to their toxicity and non-biodegradability, agricultural chemicals including pesticides and antibiotics exhibit non-selective toxicity and they accumulate in the environment including water and soil [78,79].…”
Section: Mnp-mediated Removal Of Pesticides and Antibioticsmentioning
confidence: 99%
“…According to past studies, mixing organic acids (including formic acid [39], phosphate [41], Na 2 EDTA-Mcllvaine [38,42]) with methanol [37] or ACN [43] is the most effective extraction solution with good recovery efficiency and has good reproducibility when analyzing multiple antibiotic residues in environmental matrices. Ferhi et al [34] demonstrated that ACN and citric acid-phosphate buffer can be used to efficiently extract eight antibiotics from the soil.…”
Section: Choice Of Extractantmentioning
confidence: 99%
“…Meng et al [36] developed a QuEChERS method for the residues of 20 antibiotics (17 SAs, three macrolides) in soil and obtained a good recovery efficiency of 61.4-118.9% and a lower LOQ of 2-5 μg/kg. Pan et al [38] established a QuEChERS method for 10 antibiotics (four TCs, four SAs, and two macrolides) in soil, with a recovery of 37-108% and LODs of 0.01-2.00 μg/kg. In complex soil matrices, the detection range of antibiotics in the soil varies greatly and different types of antibiotics are affected by factors such as the nature of the compound (such as solubility and adsorption distribution coefficient), the pH of the extraction solvent, and the physical and chemical properties of the soil (such as pH, organic matter, clay content, etc.).…”
Section: Introductionmentioning
confidence: 99%